Theories relating baryon asymmetry and dark matter - Morisi, Stefano; Boucenna, Sofiane M. (Frontiers in Physics, 2014)
The nature of dark matter and the origin of the baryon asymmetry are two of the deepest mysteries of modern particle physics. In the absence of hints regarding a possible solution to these mysteries, many approaches have been developed to tackle them simultaneously { leading to very diverse and rich models}. We give a short review where we describe the general features of some of these models and an overview on the general problem. We also propose a diagrammatic notation to label the different models.